THE MANAGEMENT PLANNING PROCESS, A CONSERVATION AND DEVELOPMENT TOOL FOR KSAR AIT BEN HADDOU, MOROCCO - Moriset, Sébastien; Boussalh, Mohamed (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The irst management plan for Ait Ben Haddou was produced in 2006, 19 years after the inscription of the Ksar on the World Heritage List. Despite the high number of visitors attracted to this emblematic site, the Ksar had lost its soul and was quickly deteriorating; its function had become purely commercial, and served the business interests of tour operators and souvenir dealers from outside. The anarchic movement of visitors in the ruins relected the poor management of this prestigious place, which generated no beneits for the local population. The management plan was developed over a period of one year with the active participation of the population, all the government agencies active in the region, and the heritage technicians based in Ouarzazate. This paper describes the various steps of this participatory process that involved 67 people, and brought this World Heritage jewel back into the framework of municipal development strategy. All the activities integrated in the document were suggested by the stakeholders, who slowly formulated the plan through a series of workshops, with the support of CERKAS professionals and a CRAterre expert. The full transparency in the discussions and the wide dissemination of the plan in both French and Arabic languages led to the prompt implementation of many activities, and brought positive changes into the life of the local population (water supply, cleanliness and safety, and street paving, to name a few). Five years after the preparation of the plan, we can assess its impact on private and public initiatives, and list all of the activities, which were made possible because of the better distribution of roles and responsibilities. The site has been revitalized thanks to the increased number of actors who, rather than ight for selish interests, have a common vision for the place.